Pengaruh Ukuran Perusahaan, Intensitas Modal, Dan Risiko Perusahaan Terhadap Penghindaran Pajak (Studi Empiris Pada Perusahaan Sektor Consumer Non-Cyclicals Sub Sektor Makanan dan Minuman Periode Tahun 2019-2023) - Dian Hartati; Nisak Ruwah Ibnatur Husnul (CV. ITTC INDONESIA, 2024)
This research aims to determine the influence of Firm Size, Capital Intensity, and Company Risk on Tax Avoidance. This research uses quantitative research, with secondary data. The research data source was obtained from non-cyclical consumer sector companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (BEI) for 5 years between 2019-2023. The sample selection method used in this research was a purposive sampling method so the samples obtained using this method were 11 companies. The results of this research simultaneously show that the variables of Firm Size, Capital Intensity, and Company Risk on Tax Avoidance. Partial research results: Firm Size, Capital Intensity have a significant negative influence on earnings management. Meanwhile, Company Risk variable has a significant positive effect on Tax Avoidance.